2010
DOI: 10.3758/cabn.10.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neural activity that leads to true memories, false memories, and forgetting: An fMRI study of the misinformation effect

Abstract: False memories can occur when people are exposed to misinformation about a past event. Of interest here are the neural mechanisms of this type of memory failure. In the present study, participants viewed photographic vignettes of common activities during an original event phase (OEP), while we monitored their brain activity using f MRI. Later, in a misinformation phase, participants viewed sentences describing the studied photographs, some of which contained information conflicting with that depicted in the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 49 publications
6
34
0
Order By: Relevance
“…The memory distortion effects we observed here in some ways resemble those that occur in the postevent misinformation paradigm (2), in which erroneous information presented after encoding contributes to later false memories because of source-memory confusion. During encoding of misinformation, some studies have shown recruitment of anterior and posterior midline regions that protect true memories (51), and hippocampal recruitment that supports the formation of false memories (52). Our results converge with these findings, but further indicate that neural recruitment that differentiates subsequent true and false memories during presentation of novel information depends on the extent to which memory for the original experience is reactivated rather than source confusion between the presence or absence of a lure.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The memory distortion effects we observed here in some ways resemble those that occur in the postevent misinformation paradigm (2), in which erroneous information presented after encoding contributes to later false memories because of source-memory confusion. During encoding of misinformation, some studies have shown recruitment of anterior and posterior midline regions that protect true memories (51), and hippocampal recruitment that supports the formation of false memories (52). Our results converge with these findings, but further indicate that neural recruitment that differentiates subsequent true and false memories during presentation of novel information depends on the extent to which memory for the original experience is reactivated rather than source confusion between the presence or absence of a lure.…”
Section: Discussionsupporting
confidence: 75%
“…is associated with subsequent false recognition of novel related items (e.g., alarm clock) (48), and contextual reinstatement of scene-related activity in the posterior parahippocampal cortex underlies subsequent misattributions in memory (49). Further, manipulating contextual memory engrams in the hippocampus has been shown to implant false fear memories to reactivated contexts in mice (50), which is consistent with functional neuroimaging studies in humans, pointing to the contribution of the hippocampus in the formation of false memories (51)(52)(53).…”
Section: Significancesupporting
confidence: 64%
“…Occipito-temporal regions including left middle occipital cortex showed greater activity for encoding supporting accurate recognition as opposed to gist memory, consistent with reports that visual processing supports later item-specific memory for visually presented stimuli (Baym and Gonsalves, 2010;Kim and Cabeza, 2007;Kim, 2011). Posterior LIFG was also found to be engaged in encoding predicting accurate recognition, consistent with Kim's (2011) meta-analysis of 74 subsequent memory studies.…”
Section: Item-specific and Gist Encodingsupporting
confidence: 76%
“…The same studies have found that encoding predicting true recognition engages visual cortex, e.g. bilateral fusiform gyri, inferior temporal cortex and LOC (Baym and Gonsalves, 2010;Garoff et al, 2005;Kim and Cabeza, 2007), suggesting additional perceptual processing may aid in formation of item-specific memory. These regions associated with encoding predicting true and false recognition are similar to those which in the fMRA studies discussed above were associated with sensitivity and invariance to perceptual change, respectively (Fairhall et al, 2011;Kim et al, 2009;Koutstaal et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation